Nuclear Smad6 promotes gliomagenesis by negatively regulating PIAS3-mediated STAT3 inhibition - Jiantong Jiao (Nature Portfolio, 2018)
In glioma STAT3 signaling contributes to gliomagenesis. Here, the authors show that Smad6 expression correlates with poor survival and is overexpressed in glioma cells, and regulates STAT3 activity via negatively regulating PIAS3.